GC-MS analysis of phytochemical compounds in syzygium polyanthum leaves extracted using ultrasound-assisted method - Abd Rahim, Erlena Nor Asmira; Ismail, Azlini; Omar, Muhammad Nor; Rahmat, Umi Nadhirah; Wan Ahmad, Wan Amir Nizam (Pharmacognosy Network Worldwide, 2018)
Context: Syzygium polyanthum has been traditionally formulated by the folklore for the treatment of diseases including diarrhea, rheumatism, diabetes mellitus, hypercholesterolemia, hypertension, gastritis and hyperuricemia. Normally, its phytochemicals are always extracted using solvent, maceration and steam distillation methods, but the use of ultrasound-assisted extraction (UAE) method is still not well documented. Aims: This study aims to extract the phytochemical compounds present in S. polyanthum leaves using UAE and to identify them by Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Methodology: The leaves were consecutively soaked with n-hexane, ethyl acetate and methanol in a bath sonicator to derive n-hexane (HSP), ethyl acetate (EASP), and methanol (MSP) extracts of S. polyanthum leaves and then the extracts were subjected to GC-MS analysis. Mass-spectral databases of peaks were compared with database from Wiley, NIST and FNSCC libraries for compound identification. Results: GC-MS analyses of HSP, EASP and MSP showed the presence of 21, 27, and 31 peaks, respectively. The major compound for HSP (31.912%), EASP (27.042%), and MSP (22.386%) were unknown compounds which were detected at retention time between 61.980 and 62.29 min, thus requires further characterization. Squalene and phytol were among the other major compounds present in all three extracts. Several identified compounds in the extracts such as squalene, phytol, hentriacontane, palmitic acid, α-pinene, nerolidol, linalool, α-tocopherol and β-tocopherol were known bioactive compounds. Conclusion: GC-MS analyses of n-hexane (HSP), ethyl acetate (EASP), and methanol (MSP) of S. polyanthum leaves extracts have revealed the presence of some known bioactive compounds with therapeutic importance.